2019
DOI: 10.1111/faf.12362
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Atlantic herring (Clupea harengus) recruitment in the North Sea for the past 455 years based on the δ13C from annual shell increments of the ocean quahog (Arctica islandica)

Abstract: Understanding the recruitment variability of the Atlantic herring North Sea stock remains a key objective of stock assessment and management. Although many efforts have been undertaken linking climatic and stock dynamic factors to herring recruitment, no major attempt has been made to estimate recruitment levels before the 20th century. Here, we present a novel annually resolved, absolutely dated herring recruitment reconstruction, derived from stable carbon isotope geochemistry (δ13C), from ocean quahog shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…They also reported that, across the same 100 years, the d 13 C values of Atlantic sclerosponges dropped by a similar magnitudedapproximately 0.75‰dat a rate of À0.0074 ± 0.0065‰ yr À1 (Swart et al, 2010). Estrella-Martínez et al (2019b) found that in the North Atlantic basin the rate of change for the oceanic Suess effect was variable through time, but observed a net ~1.5‰ reduction of d 13 C shell values in the bivalve Arctica islandica between 1850 and 2000 AD. The oceanic Suess effect is also more pronounced in subtropical latitudes due to the increased ventilation of the surface waters within the subtropical gyres (Eide et al, 2017;Swart et al, 2010).…”
Section: Sea Surface Cooling During the Mcamentioning
confidence: 88%
“…They also reported that, across the same 100 years, the d 13 C values of Atlantic sclerosponges dropped by a similar magnitudedapproximately 0.75‰dat a rate of À0.0074 ± 0.0065‰ yr À1 (Swart et al, 2010). Estrella-Martínez et al (2019b) found that in the North Atlantic basin the rate of change for the oceanic Suess effect was variable through time, but observed a net ~1.5‰ reduction of d 13 C shell values in the bivalve Arctica islandica between 1850 and 2000 AD. The oceanic Suess effect is also more pronounced in subtropical latitudes due to the increased ventilation of the surface waters within the subtropical gyres (Eide et al, 2017;Swart et al, 2010).…”
Section: Sea Surface Cooling During the Mcamentioning
confidence: 88%
“…Neglecting this effect may seriously hamper the interpretation of the changes in δ 13 C oto and lead to an overestimation of the metabolic rates in the most recent periods [ 74 ]. Because the decrease in the seawater δ 13 C has a nonlinear form, with a stronger decreasing trend over the last two decades, more precise methods for the correction for the Suess effect than linear approximation should be applied [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope analysis often relies on proxies for data collection. For example, using an innovative approach based on extracting isotopes from ocean quahog, Estrella-Martínez et al (2019) were able to reconstruct recruitment estimates for the North Sea herring population. Using a marine historical ecology approach, they then cross-checked these estimates with historical resources regarding fishing pressure and catch-per-unit-effort over time.…”
Section: Stable Isotopesmentioning
confidence: 99%